TREATMENT FORMULATION FOR FUTURE VICTIMS OF NARCOTICS ABUSE - Saktiawan P.; Budiono A.R.; Madjid A.; Suryokumoro H. (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
Extraordinary crimes are crimes against conscience, against human values, and capable of threatening world peace, security, and prosperity. The concept of this crime is based on the concept of international law and then modified according to the needs and formulation of crimes that exist in Indonesia into human rights crimes, narcotics crimes, and crimes against child sexuality. In the United Nations Convention Single Convention on Narcotic Drugs, 1961, and also in the United Nations Convention against illicit traffic in narcotics and psychotropic drugs in 1988, both conventions state that narcotics crime is an extraordinary crime. Against narcotics crimes, the Indonesian government carries out the function of criminal policy through the means of penalization in Law Number 35 of 2009 concerning Narcotics which applies criminal sanctions imposed for drug abuse, namely imprisonment, fines, and even the death penalty. For Narcotics addicts and Narcotics Abuse Victims, it is the person who must be helped, the help here is the rehabilitation process itself, namely medical rehabilitation and social rehabilitation. The application of an integrated assessment towards the determination of rehabilitation is alternative law enforcement with a restorative justice pattern against abusers, victims, and narcotics addicts. This research is legal research using a normative juridical approach, the data used are primary data and secondary data which are analyzed using quantitative analysis.